CDK5 Mediates Proinflammatory Effects of Microglia through Activated DRP1 Phosphorylation in Rat Model of Intracerebral Hemorrhage. (27th June 2022) - He, Mingqing; Wang, Xiaoyan; Liu, Zheng; Cui, Qiyuan; Chen, Ying; Geng, Wenqing; Zhu, Jinzhou; Shen, Jiabing
Abstract : Introduction . Cyclin-dependent kinase-5 (CDK5) is a key kinase involved in brain development and function and recently found to be involved in neuronal and astroglial apoptosis, neural stem/progenitor cell stemness, mitochondrial fission, and synaptic transmission. But the specific mechanism of CDK5-mediated anti-inflammatory remains unclear in ICH. The aim of the present study was to explore the role of CDK5 in mediating microglia activity through activated DRP1 phosphorylation in a rat ICH model. Methods . We measured behavioral change after ICH; detected the expression of CDK5 in the rat brain using immunohistochemistry; and measured the protein levels of CDK5, p35, p25, p-histone H1, and p-DRP1 using Western blot analysis. Coimmunoprecipitation analysis indicated interaction of CDK5 and DRP1. Tumor necrosis factor- α, interleukin- (IL-) 1 β, and IL-6 levels were measured using enzyme-linked immunosorbent assay (ELISA). Results . After ICH, CDK5 protein level and kinase activity increased. Western blot data showed that CDK5 expression increased from 6 h and peaked at 2 d after ICH (p < 0.05 ), and the expression of p35 was lowest at 12 h, while the expression of p25 peaked at 2 d after ICH. Besides, p-DRP1 expression change follows with CDK5 kinase activity change. Coimmunoprecipitation showed that interaction between CDK5 and DRP1 certainly exists in microglia. Then, knockdown CDK5 or p35 expression by siRNA reduced the expression level of p-DRP1. ELISA data showed that the protein levels of proinflammatory mediators, such as TNF- α, IL-1 β, and IL-6, were decreased by knockdown of CDK5. Conclusion . CDK5 may regulate DRP1 by direct phosphorylation in microglia and further induce microglia secreting proinflammation factor.